OOSM : stay home or go abroad? - Steiger, Marvin; Tao, Thuy Ngoc; Turnhout, Bram van; Wang, Wenfei; Hulsink, Willem (London : SAGE Publications Ltd, 2017)
Bruner had a revolutionary idea about a new solution for digital screen signage while working for a digital marketing company in Slovenia. When the company he was working for went bankrupt, he decided to found OOSM, a B2B digital signage start-up, with two friends. A few months later, they decided to enter the Western European market because the Slovenian market was rather small and short of investors interested in high tech start-ups. However, at that time, Bruner had a founding team from Slovenia, a technical team from Pakistan, and his product was made in China. This combination did not look favorable, not only to OOSM's potential clients but also to potential investors. Bruner knew he had a good idea, a motivated team and a quality product, but he also knew he needed credibility and validation to be able to enter the Western European market. What approach should he take in such a situation?
Originally Published InSteiger, M., Ngoc Tao, T., van Turnhout, B., Wang, W., & Hulsink, W. (2015). OOSM: Stay home or go abroad? Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; OOSM -- Case studies; Strategic planning -- Case studies; Globalization -- Case studies; Entrepreneurship -- Case studies